The Effectiveness of Internal Corporate Governance Mechanisms of SOEs and Listed Companies in South Africa - Mpele, Job (Digital Repository of Theses - SSBM Geneva, 2025)
The scope of the study focuses on the effectiveness of the board as the central structure of internal corporate governance mechanisms. The subject of this study includes a sample of four companies listed on the Johannesburg Stock Exchange (JSE) and four State Owned Enterprises (SOEs). The research findings show that there are several interrelated factors which collectively contribute to the effective functioning of internal governance mechanisms. Board failure and poor risk management were found to have been the main contributors to the ineffectiveness of internal governance mechanisms. One of the main factors which affected the effectiveness of the board, is its ability to instil a strong governance culture and value system within the organization and, with regards to SOEs especially, this has also included board stability. Boards are required to practice ethical and courageous leadership. Failure by the board to do so results in the weakening and ineffectiveness of other internal governance mechanisms. The study investigates how the corporate governance regime and governance mechanisms within South African corporations, have been influenced by the country’s unique political and socio-economic history and its need to attract foreign investors to uplift the economy and enhance economic growth, whilst also needing to deal with social and economic instability. Whilst South Africa’s governance regime includes unique corporate governance solutions and requirements aimed at responding to the unique socio-economic challenges and to meet stakeholder expectations, this does not affect or have any influence on the fundamental governance principles. The governance solutions relate to the philosophical approach towards governance, as opposed to influencing the governance framework.